Advancing microplastic and associated pollutants detection: a comprehensive review on high-sensitivity analysis using mass spectrometry techniques - González Herrera, R.; Doblado Onieva, Álvaro; Montoro-Leal, Pablo; López-Guerrero, María del Mar (Elsevier, 2026)
The accumulation of plastic waste in the environment, coupled with its prolonged persistence, has led to alarmingly high concentrations. Over time, these plastics degrade into microscopic particles, known as ‘microplastics’ (MPs), which are considered potential pollutants that threaten ecosystems and human health. Current research not only focuses on the identification and monitorization of MPs but also the determination of associated inorganic and organic pollutants since these particles can act as transport vectors of trace elements (TEs) and volatile organic compounds (VOCs). Although spectroscopic techniques have been employed, mass-spectrometry has been postulated as the most promising to achieve this purpose. This review discusses the use of MS-based techniques for detecting MPs and quantifying TEs and VOCs in MPs, including their bioaccessible fraction. Recent approaches such as gold nanoparticle (AuNPs) labeling for SP-ICP-MS and LA-ICP-MS mapping are also discussed for evaluating biological and environmental risks.
Disponible online desde el 10 de noviembre de 2025
Keywords: Espectrometría de masas; Contaminación; Microplásticos; Análisis de alta sensibilidad